SELECTION OF THE LOCATION OF UNMANNED AERIAL VEHICLES LAND BASE FOR SUPPORTING THE TASK OF THE INDONESIAN NAVY - Helmi Amrullah; Chairul Imron; Joko Purnomo; Cahya Kusuma (JOURNAL ASRO, 2022)
The Indonesian Archipelagic Sea Lanes (ALKI) which connects the Indian Ocean region with the Pacific Ocean and East Asia with Australia, has enormous consequences for efforts to implement its safeguards. An alternative is needed to optimize the current detection system. One of them is by utilizing the latest technological developments through the use of Unmanned Aerial Vehicles (UAV). The UAV capability for security and defense purposes at sea needs to be developed as an Integrated Fleet Weapon System (SSAT) to fulfill the functions of tactical reconnaissance and maritime surveillance (Surveillance). The use of the UAV can also increase strength and complement the needs of maritime patrol aircraft (Maritime Patrol Aircraft / MPA) which so far have not been fulfilled quantitatively in covering all Indonesian national jurisdiction waters. The ALKI I area is in the working area of Fleet Command I (Koarmada I). In order to optimize the placement of the ScanEagle UAV in the ALKI I area, it is very important to know the criteria for determining its location. This is also due to the limited number of ScanEagle UAVs and the large area that must be covered by these UAVs. By obtaining the location criteria for the ScanEagle UAV Landbase, it is hoped that it will make it easier to map ScanEagle placement locations at Indonesian Navy bases in the ALKI I area. ANP and TOPSIS methods. The criteria for determining the location of the UAV consist of geographical location, weather conditions, vulnerability and security as well as logistical facilities and support, with sub-criteria mountains, tall buildings, plains, sunny cloudy, rain, territorial violations, piracy crimes, smuggling, SAR, airport, ports, spare parts, maintenance, fuel and electricity availability. Based on the results of the analysis and discussion of determining the location of the selected UAV Batam Naval Base. Keywords: UAV, SSAT, Surveillance, ScanEagle, ANP, TOPSIS